The effect of varied versus constant high‐probability instructional sequences on cooperation. - Lemons, Alyssa; Wilder, David A. (Journal of Applied Behavior Analysis (John Wiley & Sons, Inc.))
We examined the effects of varied versus constant high‐probability (high‐p) instructional sequences on cooperation with a low‐probability (low‐p) task. Three children diagnosed with autism participated. We first conducted an instruction identification phase to verify high‐p and low‐p instructions and then compared varied‐to‐constant high‐p instructional sequences to improve cooperation with low‐p instructions using reversal designs. The results of the study show that the varied high‐p instructional sequence was more efficacious to increase cooperation with low‐p instructions for one participant and that the varied and constant high‐p instructional sequences were equally efficacious for the other two participants. We discuss the implications of these results for the use of the high‐p instructional sequence in practice.